'They're a very sick group of individuals': Correctional officers, emotions, and sex offenders. (August 2017) - Spencer, Dale; Ricciardelli, Rose
In this article, we analyze the politics of emotions within the occupational culture of correctional officers by focusing attention on how sex offenders are constituted as objects of fear and disgust. We draw on in-depth semi-structured interviews with 100 Canadian men and women with experience working as correctional officers in provincial prisons (e.g. New Brunswick, Ontario, Alberta, Nunavut, Prince Edward Island) to understand how sex offenders are viewed within their occupational culture. Utilizing an interpretive hermeneutic approach, this article analyzes Canadian correctional officers' interpretations of sex offenders. We show the effects of sex offenders' construction as objects of fear and disgust, in terms of their identities and positionality in the general prison population, and the level of protection and services they receive while in prison.